PARTICIPATION INSURANCE: TÜRKİYE MODEL AND ITS EXAMINATION (Third Sector Social Economic Review, 2023)
Islamic insurance (takaful), which emerged as an alternative to traditional insurance in accordance with Islamic finance principles, is called participation insurance in Türkiye. Participation insurance operating within the framework of specific models in many countries started operations in our country in 2009. The aim of this study is to provide suggestions for the development and improvement of the participation insurance model, which entered into force in 2020, unique to our country, by analyzing different problem areas. In this context, traditional insurance will be explained from an Islamic perspective and the reasons for the emergence of participation insurance will be revealed, and the basic principles of participation insurance and the commonly used models in practice will be explained. Subsequently, the participation insurance model specific to our country, which was designed as a new model, will be discussed. Finally, suggestions will be made for the development of participation insurance in our country. It is recommended that the current legislation be reviewed and various flexibility should be given to participation insurance companies in practice, in terms of issues such as the new participation legislation adopting a legislative structure that will offer flexibility rather than a casuistic (overly prescriptive) legislative design.
Keywords: Participation insurance; Takaful; Islamic insurance; Türkiye model; Participation finance